Obstetric outcome in pregnancy complicated by ovarian cysts - S. R., Sheela; P. N., Sreeramulu; L., Poonguzhali; K., Arulselvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ovarian masses are diagnosed in 0.5-1% pregnancies. During pregnancy ovarian cysts can undergo: resolution of the cyst, change of ultrasound pattern, occurrence of ovarian torsion and intra-cystic haemorrhage or rupture. Ovarian masses (esp torsion) is a cause of pain abdomen during pregnancy. The choice of treatment is mainly conservative, provided the patient is asymptomatic. Dilemma in management arises when the patient is symptomatic. Optimal timing for a planned surgery is the second trimester as it is shown to have least neonatal outcome. The objective of this study was to evaluate management options for ovarian cyst in pregnancy and its effect on outcome of pregnancy. Methods: This study was conducted for 2 years from June 2014 to June 2016, at RL Jalappa Hospital, Kolar. A total of 46 pregnant women were included. The pregnancy outcome and the management used were studied. Also studied were the complications most likely to occur in pregnancies complicated by ovarian masses ovarian masses. Results: Out of 46 patients, 2 (4.3%) patients with ovarian cyst torsion underwent emergency laparotomy. 8 patients underwent surgery (6 in 2nd trimester and 2 at term) for various complications. Only one patient had miscarriage and remaining patients continued till term. Histopathological report of all the masses excised were obtained and 6 were reported to be benign serous cystadenomas,1 benign mucinous cystadenoma and 3 simple cysts. Conclusions: Optimal management for ovarian cyst is conservative in pregnancy provided patient remain asymptomatic and characteristic of cyst are consistent with benign pathology. Surgical management is to be reserved for symptomatic patient.